Meditative and non-meditative mindfulness-based interventions for mind and body - Kyriaki Giannou; Michail Mantzios (BMC, 2023)
Abstract The present editorial synopsises the benefits and challenges in meditative and non-meditative mindfulness practices and explores shorter and more creative approaches in mind-body interventions, emphasizing inclusivity and evidence-based practices. This collection, launched in BMC Complementary Medicine and Therapies, aims to bring together research on a variety of mindful practices, to discuss their role in supporting wellbeing.